Characterisation of P2Y(2) receptors in human vascular endothelial cells using AR‐C118925XX, a competitive and selective P2Y(2) antagonist - Muoboghare, Markie O. (Br J Pharmacol, 2019)
BACKGROUND AND PURPOSE: There is a lack of potent, selective antagonists at most subtypes of P2Y receptor. The aims of this study were to characterise the pharmacological properties of the proposed P2Y(2) receptor antagonist, AR‐C118925XX, and then to use it to determine the role of P2Y(2) receptors in the action of the P2Y(2) agonist, UTP, in human vascular endothelial cells. EXPERIMENTAL APPROACH: Cell lines expressing native or recombinant P2Y receptors were superfused constantly, and agonist‐induced changes in intracellular Ca(2+) levels monitored using the Ca(2+)‐sensitive fluorescent indicator, Cal‐520. This set‐up enabled full agonist concentration–response curves to be constructed on a single population of cells. KEY RESULTS: UTP evoked a concentration‐dependent rise in intracellular Ca(2+) in 1321N1‐hP2Y(2) cells. AR‐C118925XX (10 nM to 1 μM) had no effect per se on intracellular Ca(2+) but shifted the UTP concentration–response curve progressively rightwards, with no change in maximum. The inhibition was fully reversible on washout. AR‐C118925XX (1 μM) had no effect at native or recombinant hP2Y(1), hP2Y(4), rP2Y(6), or hP2Y(11) receptors. Finally, in EAhy926 immortalised human vascular endothelial cells, AR‐C118925XX (30 nM) shifted the UTP concentration–response curve rightwards, with no decrease in maximum. CONCLUSIONS AND IMPLICATIONS: AR‐C118925XX is a potent, selective and reversible, competitive P2Y(2) receptor antagonist, which inhibited responses mediated by endogenous P2Y(2) receptors in human vascular endothelial cells. As the only P2Y(2)‐selective antagonist currently available, it will greatly enhance our ability to identify the functions of native P2Y(2) receptors and their contribution to disease and dysfunction.